1999
DOI: 10.1097/00005176-199907000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Lymphonodular Hyperplasia As a Sign of Food Allergy in Children

Abstract: Preliminary observations showed that lymphonodular hyperplasia of the duodenum or the colon is related to the gastrointestinal type of food allergy to basic foodstuffs. Further research is needed to define this finding as a separate entity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
40
0
1

Year Published

2001
2001
2009
2009

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 16 publications
1
40
0
1
Order By: Relevance
“…1,2 Furthermore, it can occur in school-age children, 3,5,12 who frequently exhibited LNH of the colon, which is now considered a possible marker of FH in children. [3][4][5][6][7][8] On this basis, we performed a study in adults to search for a possible relation between FH, proctitis, and LNH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Furthermore, it can occur in school-age children, 3,5,12 who frequently exhibited LNH of the colon, which is now considered a possible marker of FH in children. [3][4][5][6][7][8] On this basis, we performed a study in adults to search for a possible relation between FH, proctitis, and LNH.…”
Section: Discussionmentioning
confidence: 99%
“…3 Others described LNH as an endoscopic marker of cow's milk allergy in children. [4][5][6][7][8] This prospective study showed that rectal bleeding and intestinal LNH can be caused by FH in adult patients.…”
mentioning
confidence: 84%
“…17,18 The endoscopic and immunohistochemical findings of duodenal biopsies confirm our previous findings concerning the mucosal state in the duodenum of patients with CMSE. We found LNH in one third of the CMSE subjects and a significant elevation in the densities of intraepithelial CD3, ab-and gd-positive T cells in the duodenum, 12,23 indicating that CMSE should be included in the differential diagnostic consideration when increase in IELs, a hallmark of CD, 18 is seen in biopsies, or LNH is seen at endoscopy. In CMSE, the concentrations of GrA and GrB showed most discriminative values in comparison with control subjects.…”
Section: Discussionmentioning
confidence: 75%
“…11 In CMSE the distribution of mucosal changes varies, and in many cases, in addition to the abnormalities in the proximal small intestine, ileal and colon mucosa may also show an increase in IELs. 23 We thus speculate that, like the extent of villous changes in CD associating with serum GrA levels, the serum concentration of GrB in CMSE may depend on the extent of mucosal lesions; higher values possibly associate with a more extensive intestinal immune response. However, more studies are necessary to confirm this idea.…”
Section: Discussionmentioning
confidence: 79%
“…Food allergy with typical reflux symptoms provides specific endoscopic and histological pictures of mucosa of upper gastrointestinal tract [14,16,25,26]. This is still the object of numerous studies on the youngest children with food hypersensitivity and GER, whereas in older children with persistent allergy [1,13,14,16,22,25,27,28].…”
Section: Introductionmentioning
confidence: 99%